Labour- or Talent Shortage? – Exploring the Conceptual Differences for Effective Practice - Héder, Mária (International Journal of Engineering and Management Sciences, 2017)
Regarding the issue of unemployment, a number of researches have been done at national level. Deliberately, public awareness has a particular emphasis on this situation from employee aspect. However, from the labour market point, the issue of labour shortage has just as serious consequences like unemployment, although its extent is detectable mainly at employers side. Nowadays, employers are negatively affected by the very nature of labour shortage, and the issue of talented shortage became the most sensitive issue. It has a prominent importance to distinguish labour and talent shortage. Despite the fact that these phrases are frequently used as synonyms these have different meanings. The aim of my research is to determine main differences between labour and talent shortage by seconder data to help in correct use and understanding at organisational level.